Peningkatan Keaktifan Belajar Siswa pada Pembelajaran PKN Melalui Penerapan Metode Kerja Kelompok di MI Miftahul Athfal - Fadil, Khaidir; Muslimah, Mutiara; Nawawi, Kholil (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
This study aimed to determine how to increase student learning activeness in Civics learning through the application of group work methods. The research method used was Classroom Action Research (PTK). The subjects were 37 students, the research data sources were obtained from qualitative data in the form of data from observations of teacher and student activities and quantitative data in the form of student learning outcomes test data. The results of this study can be seen from the increased student activeness in cycle I there were 20 students who were active or in the good category (54%) and 17 students who were less with an average student learning activeness (65.4%). In cycle II, student learning activeness increased with 32 active students (86%), moderately active students, it can be concluded that there is an increase in student learning outcomes through the group work method in Civics learning class V